The Problematics of Learning The History of Islamic Culture in The 2013 Curriculum in Madrasah Aliyah Isy Karima Karanganyar Solo - Moh Shohibul Umam; Rahmat Arofah Hari Cahyadi (Studia Religia : Jurnal Pemikiran dan Pendidikan Islam, 2020)
The thing that must be considered in learning Islamic Cultural History is that the management of teaching must be properly organized and systematically designed. In addition, teachers must be good at packaging Islamic Cultural History lessons and provide insightful awareness of history in accordance with their era. So, learning Islamic Cultural History so far that seems boring can be transformed by the teacher into fun and entertaining lessons. The formulation of the problems in this study are: 1). How is the study of Islamic Cultural History in the 2013 Curriculum at Madrasah Aliyah Isy Karima Karanganyar Solo? 2). How is the problem of learning the History of Islamic Culture in the 2013 Curriculum at Madrasah Aliyah Isy Karima Karanganyar Solo? 3). How are the efforts to overcome the problems of Islamic Cultural History in the 2013 Curriculum at Madrasah Aliyah Isy Karima Karanganyar Solo? This research uses qualitative research with a case study approach. While the data collection techniques used interviews, observation, and documentation. The data analysis techniques include data reduction, data presentation, and conclusion or verification. To check the validity of the data, it uses observation and triangulation persistence. After this research was conducted, several conclusions could be drawn: 1). Learning the History of Islamic Culture at Madrasah Aliyah Isy Karima Karanganyar Solo uses discussion, lecture and question and answer methods. 2). There are learning problems faced by teachers, namely the use of lesson plans, determining media, determining methods, limited learning resources, class management, heterogeneity of students, and learning evaluation. While the problems faced by students, namely learning at the end of class hours, student interests, class conditions, and learning difficulties. 3). Some efforts to overcome the problems experienced by teachers are sharing with other teachers, attending trainings, looking for other learning resources, forming learning contracts, cooperating with other parties, making approaches to students.